Prehabilitation in Alcohol Dependence as a Treatment Model for Sustainable Outcomes. A Narrative Review of Literature on the Risks Associated With Detoxification, From Animal Models to Human Translational Research - Kouimtsidis, Christos; Duka, Theodora; Palmer, Emily; Lingford-Hughes, Anne (Frontiers in Psychiatry, 2019)
In this review paper we discuss how the overarching concept of pre-habilitation is applicable to alcohol dependence. Central to pre-habilitation are the concepts of expected harm or risks and pro-active planning to eliminate the harm or cope with the risks. We review the evidence from animal models, psychological experimental studies, as well as pharmacological studies, on the potential risks and harms associated with medically assisted alcohol detoxification and the current treatment paradigm for alcohol dependence. Animal models provide an approximation mostly of the physical aspect of alcohol withdrawal and detoxification process and make predictions about the development of the phenomena in humans. Despite their limitations, these models provide good evidence that withdrawal from chronic ethanol induces cognitive impairment, which is worsened by repeated bouts of withdrawal and that these impairments are dependent on the duration of alcohol withdrawal. Initial clinical observations with alcohol dependent patients confirmed increased incidence of seizures. Over the last years, evidence has accumulated to show that patients who have undergone repeated episodes of withdrawal also show altered affect, increased craving as well as significant deterioration of cognitive abilities, when compared to patients with fewer withdrawals. Alcohol dependence is associated with tolerance and withdrawal with neuroadaptations in GABA-A and glutamatergic N-methyl-D-aspartate (NMDA) receptors playing key roles. Dysregulation of the NMDA receptor system is thought to underpin alcohol related memory impairments. Finally we discuss the Structured Preparation for Alcohol Detoxification (SPADe) as an example of how pre-habilitation has been applied in clinical practice. We discuss the importance of partial control over drinking as an interim step towards abstinence and early introduction of lifestyle changes for both the person and the immediate environment prior detoxification and while the person is still drinking.